Virus-Associated Nucleases: Location and Properties of Deoxyribonucleases and Ribonucleases in Purified Frog Virus 3 - Kang, H. S. (1972)
At least three nuclease activities are associated with purified frog virus 3. These activities are endodeoxyribonuclease (pH 7.5, double-stranded [DS] and single-stranded [SS] deoxyribonucleic acid [DNA]); endodeoxyribonuclease (pH 5.0, DS and SS DNA); endoribonuclease (DS and SS ribonucleic acid [RNA], pH 7.5). These activities are not adsorbed to the surface of the virion but are within the viral capsid and require detergent disruption of virions to unmask enzyme activity. Only one activity, deoxyribonuclease (pH 5.0, SS and DS DNA) appears to be core-associated after detergent disruption of virions. The ribonuclease degrades poliovirus replicative-form RNA, reovirus native RNA, and poly(I) poly(C) to a product with a sedimentation coefficient of about 6S. Qβ 6S DS RNA and 4S transfer RNA are not degraded. The ribonuclease appears to be a late function of the virus and is elicited in a soluble form as well as a virus-associated form.